(untitled) (Research, Society and Development, 2020)
The difficulties presented to the contents of botany during the teaching and learning process are notorious. Among the numerous reasons, the need to use teaching materials to assist in the practical and theoretical activities essential for dynamic and interactive classes stands out. This work aims to evaluate the material produced entitled "Guide to practical classes in Botany" in order to contribute to the knowledge of plants and their morphological characteristics. The topics were defined through a bibliographic search in the specific literature, in addition to the analysis in textbooks from the first to the third year of high school, available in public, municipal, state and federal schools in the municipality of Buriticupu-MA. After the organization and formatting, the files were printed and delivered, together with an evaluative questionnaire, to the teachers graduated and working in high school rooms in the city, in order to assess the feasibility of use for the Biology classes. The results showed the main positive points: good context, easy to understand language and visual resources endemic to the region. It is concluded that the material produced is significant to provide dynamic and attractive classes, in addition to arousing the interest of students in plant morphology.